The Spanish Golden Age Literature in Lengua castellana y literatura Secondary School Textbooks: Editorial Projects outside the Curriculum and Inclusion - Rodríguez Ortega, Davinia (Didáctica. Lengua y Literatura, 2022)
The present study intends to examine various manuals of 3rd course of Educación Secundaria Obligatoria of the subject of Lengua castellana y literatura (specifically the topics dedicated to the literature of the Golden Age) in Spain to check to what extent the guidelines set by educational legislation are followed in the curriculum. To do this, four textbooks from leading publishers will be used as a sample, which will be examined from several fragments extracted from a study designed by Braga Blanco and Belver Domínguez (2016). Its emphasis will be placed on the analysis of the messages, especially the content, as well as on the comparison of the curricular proposal of the manuals against the one decreed by the official curriculum and the comparison between materials from different publishers. As a result, it will be possible to observe how a corpus of authors and works inherited from the 19th century continues to be maintained, with canonical figures and other excessive forgotten, even today, as the women writers who carried out their artistic work in the Spanish 17th century.
Keywords: lengua castellana y literatura; textbooks; Enseñanza Secundaria Obligatoria; Golden Age; curriculum